Kampanye Public Relations “Ngopi tapi Go Green” di RBoJ Coffee - Firstsishella Shabrina Putri Mulia; Rizky Fauzi (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Cutlip and Gleen Broom who defined problems, planning, initiating and communicating, and evaluating activities. The literature review used in the coverage of this work is public relations, public relations campaigns, green campaigns,